Synthesis of Phthalimide Imine Derivatives as a Potential Anticancer Agent - Hayman Sardar Abdulrahman; Mohamed Hassan Mohammed; Lina A. Al-Ani; Mohd Hafiz Ahmad; Najihah M. Hashim; Wageeh A. Yehye (Journal of Chemistry)
The outstanding evidence of phthalimide pharmacophore in securing enhanced biological activities had encouraged further research and development into phthalimide-based derivatives as potential new drugs. In this study, phthalimide core was hybridized with aldehydes giving integrated imines displaying different types of functionalities and at alternating positions. The resulting compounds, therefore, provide an innovative window to explore possible differential biological effects as antioxidants and anticancer agents. A total of sixteen compounds were synthesized, and each was verified by FT-IR, H NMR, C NMR, and MS characterization. Herein, a facile single-step synthesis method was employed substituting the conventional two-step chemical production routes. Among the sixteen tested compounds, the H7 compound with hydroxyl phenolic group has shown an eminent antioxidant activity with a 19.52% decrease to the IC50 value compared to that of the control standard BHT antioxidant. On the other hand, the halogenated H6 Schiff base structure was successful in securing effective cancer inhibition to both colon and breast cancer cell lines, while maintaining selective action toward normal tissues. Results have collectively indicated the importance and impactful effects of functional groups position and types within similar basic structures, in directing different biological outcomes.